Neutralization of complement regulatory proteins augments lysis of breast carcinoma cells targeted with rhumAb anti-HER2 - Jurianz, Katrin; Maslak, Sabine; Garcia-Huttenlocher, Helena Isabel; Fishelson, Zvi; Kirschfink, Michael (Immunopharmacology, 1999)
The capacity of recombinant human monoclonal anti-p185HER2 IgG (rhumAb anti-HER2) to activate human complement was investigated. Complement activation by rhumAb anti-HER2 on various human breast carcinoma cell lines resulted in deposition of complement proteins on these cells. Complement activation was also observed in a solid-phase binding assay, in which purified p185HER2 was immobilized onto a microtiter plate. rhumAb anti-HER2 induced some complement-mediated tumor cell lysis by rabbit complement, but not by human complement. Analysis of membrane complement regulatory proteins (mCRP) on breast carcinoma cells revealed a heterogenous expression of CD46, CD55 and CD59. After blocking the mCRP activity with specific antibodies, rhumAb anti-HER2 induced about 15% lysis of p185HER2-expressing tumor cells. Tumor cell sensitization with rabbit polyclonal anti-tumor antiserum following mCRP neutralization, augmented cell lysis from 10 to 80%. Expression of mCRP was upregulated by treatment with PMA, and correlated with increased protection of the tumor cells from complement lysis. These results suggest that humanized antibodies like rhumAb anti-HER2 promote complement activation leading to tumor cell phagocytosis and cell-mediated cytotoxicity. They further demonstrate that a successful tumor immunotherapeutical approach, based on antibody and complement treatment, requires mCRP neutralization.
Gesehen am 17.02.2021